Association of dietary patterns with hemoglobin levels among pregnant women in Asahan Regency - Tika Andriani; Fitriyono Ayustaningwarno; Ahmad Syauqy (AcTion: Aceh Nutrition Journal, 2026)
Anemia during pregnancy is a serious public health issue that can adversely affect both mothers and fetuses. Dietary patterns play a crucial role in determining the hemoglobin levels in pregnant women. In Indonesia, anemia among pregnant women remains highly prevalent, affecting approximately 48.9% of them.  This study aimed to analyze the association between dietary patterns and hemoglobin levels in pregnant women. This study employed a cross-sectional design with a purposive sampling technique, involving 170 pregnant women in Asahan Regency from April to May 2025. Dietary data were collected using a semi-quantitative food frequency questionnaire (SQ-FFQ), and hemoglobin levels were measured using a hematology analyzer. Multivariate regression analysis was performed to examine the association between each dietary pattern and the hemoglobin level. Dietary patterns high in both animal and plant protein were significantly associated with increased hemoglobin levels in pregnant women (95% CI: 12.02–12.7; p<0.001). Conversely, consumption of diets high in sugar and fat was significantly associated with decreased hemoglobin levels (95% CI: 11–11.8; p<0.001). In conclusion, diets rich in animal and plant proteins are positively associated with higher hemoglobin levels in pregnant women. These findings highlight the importance of protein-based nutritional interventions in preventing anemia during pregnancy.